PENGARUH MEDIA 3D BERBANTUAN WEB ASSEMBLR TERHADAP HASIL BELAJAR MATERI PENGENALAN KOMPONEN KOMPUTER PADA SISWA SMP - Monica, Frisca; i, Pramudiyanti; Rinaldi, Daniel; Fadli, Radinal (Information Technology Education Department, 2025)
Digital technology requires the world of education to utilize interactive and innovative learning media. Web-based three-dimensional (3D) visualization media can help students understand abstract concepts more concretely. In computer science education, particularly in the introduction to computer components, students still find it difficult to recognize the actual form and function of components. This study aims to determine the effect of web-based 3D media using Assemblr on the learning outcomes of seventh-grade students at SMP Negeri 36 Bandar Lampung. The research method used was an experimental method using a quasi-experimental model with a pretest-posttest equivalent control group research design involving two classes, each with 34 students. The instrument used was 20 multiple-choice questions that had been tested for validity and reliability (α = 0.801). The results showed a significant increase in the learning outcomes of students in the experimental class. The average pretest score for the experimental class was 46.32, which increased to 81.91 on the posttest. This comparison resulted in an average N-Gain score of 0.6428, which is categorized as moderate. The results of the independent sample t-test also showed a Sig. value of 0.000, proving that there was a significant difference between the learning outcomes of the two groups. Thus, it can be concluded that the use of web-based 3D media assemblr has a significant effect on student learning outcomes in computer component introduction material.